2012
DOI: 10.1371/journal.pone.0040836
|View full text |Cite
|
Sign up to set email alerts
|

BAT3 Regulates Mycobacterium tuberculosis Protein ESAT-6-Mediated Apoptosis of Macrophages

Abstract: HLA-B-associated transcript 3 (BAT3), also known as Scythe or BAG6, is a nuclear protein implicated in the control of apoptosis and natural killer (NK) cell-dendritic cell (DC) interaction. We demonstrate that BAT3 modulates the immune response by regulating the function of macrophages. BAT3 is released by macrophages in vitro and it down-regulates nitric oxide and proinflammatory cytokines release in IFN-γ and LPS stimulated macrophages. Furthermore, Mycobacterium tuberculosis-derived protein ESAT-6 (Rv3875) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…It has been shown that BAT3/BAG6 can be released from tumor cells in response to stress signals [42]. Both BAT3/ BAG6 as well as UBD/FAT10 expression was shown to be increased during inflammatory response [21,43]. This may be caused by the release of proinflammatory factors from macrophages of THRLBCL [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that BAT3/BAG6 can be released from tumor cells in response to stress signals [42]. Both BAT3/ BAG6 as well as UBD/FAT10 expression was shown to be increased during inflammatory response [21,43]. This may be caused by the release of proinflammatory factors from macrophages of THRLBCL [12].…”
Section: Discussionmentioning
confidence: 99%
“…With NKp30 activated by BAG6, we identified one important factor critically involved in RIG-I-induced EV-mediated antitumor activity in the human system. However, since NKp30 is a pseudogene in the murine system and is not expressed as a functional receptor, the RIG-I-EVs mediated NK activating effects in vivo might be mediated by unknown receptors distinct from NKp30 that have been reported to exist in mice but which have not been identified yet 45 . Thus, further work is needed to analyze the role of RIG-I induced EVs and BAG6 in the mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Under certain conditions and by mechanisms that are not completely understood, BAG6 can be released from cells into the extracellular environment. 10,24,25 The protein can be expressed on the surface Submitted January 7, 2013; accepted February 26, 2013. Prepublished online as Blood First Edition paper, March 18, 2013; DOI 10.1182 DOI 10.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Under certain conditions and by mechanisms that are not completely understood, BAG6 can be released from cells into the extracellular environment. 10,24,25 The protein can be expressed on the surface of exosomes to engage NKp30 and to activate NK cells. 10,25 Exosomes are 50 to 100 nm microvesicles that originate from intracellular multivesicular bodies and are produced by many cell types.…”
Section: Introductionmentioning
confidence: 99%